Cognition: rules and contact with contingencies - Simonassi, Lorismário Ernesto (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Different conceptions about consciousness as a cognitive event are described and compared. The literature about possible relationships between stimulus discrimination and description of the contingency involved is reviewed. Data concerning: 1. the possibility of human subjects solving problems without being able to describe them; 2. the description of a contingency as a pre-requisite for the occurrance of problem solving; 3. whether an increase in problem solving behavior rates occurs before or after the description of a contingency are presented. Experimental data that indicate the possibility of solving problems without previous description of the contingencies involved are presented.